Depletion of reactive oxygen species induced by chlorogenic acid triggers apoptosis-like death in Escherichia coli. (4th May 2018) - Lee, Bin; Lee, Dong Gun
Abstract: Chlorogenic acid (CGA) is a phenolic compound with various health-promoting properties, including antioxidant effects and a wide range of antibacterial activities. However, the antibacterial mechanism remains unclear. We investigated the underlying mode of action of CGA against Escherichia coli, which shows bacterial apoptosis-like death. Cells treated with CGA showed apoptotic features such as membrane depolarisation, caspase-like protein expression, increased intracellular Ca 2+ levels, phosphatidylserine externalisation, and DNA fragmentation. In contrast to common bacterial apoptosis-like death, which is caused by reactive oxygen species (ROS) accumulation, CGA depleted intracellular ROS. Because ROS are important intracellular signalling molecules, and ROS depletion may affect bacterial intracellular signalling pathways, leading to cell death. To determine whether deficiencies in intracellular ROS cause apoptosis-like death, the cells were treated with H2 O2 after CGA treatment. H2 O2 restored depleted intracellular ROS levels to similar levels as in untreated cells, and cell viability was increased compared to CGA-treated cells. Moreover, apoptotic features were attenuated in H2 O2 post-treated cells. These results demonstrate that CGA induces bacterial apoptosis in E. coli and intracellular ROS depletion is a core regulator in the progression of bacterial apoptosis-like death.